Amplitude Changes during Ventricular Fibrillation: A Mechanistic Insight - Caldwell, Jane C.; Burton, Francis; Cobbe, Stuart; Smith, Godfrey (Frontiers in Physiology, 2012)
Introduction: Clinically in ventricular fibrillation (VF), ECG amplitude and frequency decrease as ischemia progresses and predict defibrillation success. In-vitro ECG amplitude declines without ischemia, independent of VF frequencies. This study examines the contribution of cellular electrical activity and global organization to ECG amplitude changes during VF. Methods and results: Rabbit hearts were Langendorff-perfused (40mL/min, Tyrode’s solution) and loaded with RH237. During VF, ECG and epicardial optical action potentials were recorded (photodiode array; 256sites, 15×15mm). After 60s of VF, perfusion was either maintained, global ischemia produced by low-flow (6mL/min), or solution [K+]o raised to 8mM. Peak-to-peak amplitude was determined for all signals. During VF, in control, ECG amplitude decreased to a steady-state ( 57% baseline), whereas in low-flow steady-state was not reached with the amplitude continuing to fall to 33% of baseline by 600s. Optically, LV amplitude declined more than RV, reaching significance in control (LV vs. RV; 33+/-5% vs. 638%, p<0.01). During VF in 8mM[K+]o, amplitude changes were more complex; ECG amplitude increased with time (105±13%), whilst LV amplitude decreased (60±15%, p<0.001). Microelectrode studies showed amplitude reduction in control and 8mM[K+]o (to 79% and 93% baseline respectively). Evaluation of electrical coordination by cross-correlation of optical signals showed as VF progressed coordination reduced in control (baseline 0.36±0.02 to 0.28±0.003, p<0.01), maintained in low-flow (0.41±0.03 to 0.37±0.005, p=NS) and increased in 8mM[K+]o (0.36±0.02 to 0.53±0.08, p<0.05). Conclusions: ECG amplitude decline in VF is due to a combination of decreased systolic activation at the cellular level and increased desynchronization of intercellular electrical activity.